Vascular endothelial growth factor induces the migration of human airway smooth muscle cells by activating the RhoA/ROCK pathway - Chengtian Lv; Yuwen Huang; Ruirong Yan; Yuanmei Gao (BMC Pulmonary Medicine, 2023)
Abstract Background Airway remodeling due to increased airway smooth muscle cell (ASMC) mass, likely due to enhanced proliferation, hypertrophy, and migration, has been proven to be highly correlated with decreased lung function in asthma patients. Vascular endothelial growth factor (VEGF) mediates vascular and extravascular remodeling and inflammation and has been proven to be involved in the progression of asthma. Previous studies have focused on the effects of VEGF on ASMC proliferation, but few researchers have focused on the effects of VEGF on human ASMC migration. The purpose of this study was to explore the effect of VEGF on the migration of ASMCs and its related signaling pathway mechanism to provide evidence for the treatment of airway remodeling. Methods We examined the effects of VEGF induction on ASMC migration and explored the mechanisms involved in ASMC migration. Results We found by wound healing and Transwell assays that VEGF promoted ASMC migration. Through the Cell Counting Kit-8 (CCK-8) experiment, we found that VEGF had no significant effect on the proliferation of ASMCs, which excluded the involvement of cell proliferation in the process of wound healing. Moreover, a cellular immunofluorescence assay showed that VEGF promoted F-actin reorganization, and Western blotting showed that VEGF improved RhoA activation and myosin phosphatase targeting subunit-1 (MYPT1) and myosin light chain (MLC) phosphorylation in ASMCs. Treatment with the ROCK inhibitor Y27632 significantly attenuated the effects of VEGF on MYPT1/MLC activation and cell migration. Conclusion In conclusion, the results suggest that the promigratory function of VEGF activates the RhoA/ROCK pathway, induces F-actin reorganization, improves the migration of ASMCs, and provides a better rationale for targeting the RhoA/ROCK pathway for therapeutic approaches in airway remodeling.